Oral anticancer agents: a prospective pilot study of a patient educational surgery run by a pharmacist and a nurse. Issue 2 (12th March 2012) - Conde-Estévez, D.; Gómez-Ulloa, D.; Bundó, A. Vila; Antonio, J. Mateu-de; Florit, M.; Ferrándiz, R. Blat; Salas, E.; Albanell, J.
Abstract : Background: There has been a remarkable growth in approved oral anticancer agents (OAA) in recent years. This situation involves the pharmacist as a key part of the interdisciplinary team ensuring the safety and an adequate knowledge of the treatment with OAA. This may enhance compliance and reduce adverse events. A patient educational surgery was established by a team of a pharmacist and a nurse (PESPN). Purpose: To describe the first PESPN patients. To compare the number of calls received by the continuing oncology care unit (COCU) before and after the establishment of PESPN. Materials and methods: Prospective observational study from 2010 to present in a tertiary hospital. The authors included all patients initiating OAA. The information tools employed were validated leaflets about each drug, others leaflets related to symptoms management and personalised treatment calendars. Furthermore, The authors checked potential interactions between OAA and other concomitant treatment. Data collected: demographics, family support, KI (Karnofsky index), comorbidities, disease, staging, treatment type, information support, concomitant medicines, interactions prevented, number of phone calls received by the COCU. Results: 34 patients. No. (%): women: 20 (60.6%); age (mean 66.5+/-15.2); family support 28 (84.8%); KI 90-100%: 28 (84.8%); comorbidities: 20 (60.6%); disease: breast 14 (42.4%), lung 9 (27.2%), CNS: 8 (24.2%), colon: 2 (6.1%); stageIV: 32(97.0%); metastatic: 23(69.7%), adjuvant: 10 (30.3%); indication for OAA: progression by imaging: 15 (45.5%), first-line treatment: 13 (39.4%), biochemical progression: 3 (9.1%), patient preference: 2 (6.1%), pathological progression: 1(3.0%); OAA: vinorelbine: 11(33.3%), capecitabine: 8 (24.2%), temozolomide: 8 (24.2%), topotecan: 3 (9.1%), erlotinib: 2(6.1%), gefitinib 1(3.0%); information tools: OAA leaflets: 31(93.9%), personalised calendar: 4(12.1%), others 3(9.1%); concomitant medicines: 32 (97.0%)(mean 3.8+/-2.2); complementary medicine: 2 (6.1%); total interactions: 6(18.2%); erlotinib-omeprazole:3(9.1%), erlotinib-acenocoumarol: 1(3.0%), capecitabine- acenocoumarol (3.0%), valproic-temozolomide: 1(3.0%). Phone-calls received by COCU: year 2009:1320 versus year 2010:1087 (17.7% reduction). Conclusions: The typical patient profile was a woman with metastatic breast cancer initiating OAA after imaging progression. The treatment most dispensed was vinorelbine and the patients were given information leaflets specifically about the OAA. Almost all patients were on concomitant medicines and potential interactions were prevented. There was a significant reduction in the number of telephone inquiries received by COCU.